2012
DOI: 10.5402/2012/802648
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Flatus and the Associated Risk Factors in Iranian Women: A Main Research Article

Abstract: Objective. The aim of the study was to determine the prevalence of vaginal flatus and some related risk factors in Iranian women. Methods. After conducting a pilot study, a sample size of 1000 subjects of 18 to 80 years was determined; of those 58 were unable to cooperate for various reasons. Age, parity, marital status, birth history, body mass index, and the weight of the largest newborn were collected. After a full gynecologic examination looking for pelvic organ prolapse, patients were asked about vaginal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…The rate of vaginal wind in our study was much higher than previously reported rates, which vary between 12.8% and 20%. 3,4 One possible explanation for this discrepancy is that we assessed the prevalence of vaginal wind in a population of women with pelvic floor dysfunction, whereas other authors assessed the prevalence of vaginal wind in general gynecologic populations. 3,4 Our results suggest that vaginal wind may be related to pelvic floor dysfunction, but not necessarily to POP.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…The rate of vaginal wind in our study was much higher than previously reported rates, which vary between 12.8% and 20%. 3,4 One possible explanation for this discrepancy is that we assessed the prevalence of vaginal wind in a population of women with pelvic floor dysfunction, whereas other authors assessed the prevalence of vaginal wind in general gynecologic populations. 3,4 Our results suggest that vaginal wind may be related to pelvic floor dysfunction, but not necessarily to POP.…”
Section: Discussionmentioning
confidence: 91%
“…These results are consistent with those previously reported by other authors who also found that vaginal wind was associated with distress and embarrassment. 2,4 One main reason why vaginal wind may be bothersome is due to the auditory nature of this condition and the potential for confusion with anal flatulence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is not uncommon for women to experience vaginal wind, which is an underrated symptom [ 3 , 4 ]. Although the vagina air is very similar to anal exhaust, and the gas is usually harmless and odorless, the sound of the vaginal exhaust can be embarrassing and distressing for women with the condition and can even lead to social isolation [ 5 , 6 ]. Slieker-ten Hove et al reported that in the general population of women aged 14–85 years, the incidence of vaginal wind was 12.8% [ 3 ].…”
Section: Introductionmentioning
confidence: 99%